Body-book: weaving knowledge at the crossroads of artifice and asceticism (Revista de Ensino em Artes, Moda e Design, 2025)
This article is based on qualitative theoretical-practical research that aims to investigate the interweavings experienced in artisanal bookbinding, a device for shaping the book object, and in yoga as a means of asceticism in life. These topics are presented as—more than objects of study—an epistemological approach. Thus, the article seeks to elaborate on principles common to artisanal and ascetic practices, perceived as potential resources for the production of knowledge in alteritarian dynamics and polyrational exercises of conversations between feelings, thoughts, and actions of different traditions. The identified principles are based on skills developed through the ability to sustain a state of presence and attentive, careful repetition, open to the unexpected. These techniques involve engaging body, mind, and spirit in consistent and conscious processes that provoke intuition, understood here as access to knowledge made possible precisely by the persistence of this engagement. Procedures operated in time, rhythm, and with rigor that enable reflection during the process and create spaces for the emergence of new modes of (co)existence, beyond a regime of hierarchies and obligations. Connections are made through the assumption of the condition of not knowing and incompleteness. Book and body share a spine, the support of their physical and motor manifestation, and a vehicle for expansion and unfolding in the subtle realm.
Keywords: book; body; presence; repetition